Multi-gene co-mutations of BRAF with TERT, PIK3CA, or TP53 are powerful predictors of central lymph node metastasis in papillary thyroid carcinoma - Yu, Qing; Liu, Han (Frontiers in Endocrinology, 2026)
BackgroundThe accurate preoperative prediction of lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) poses a significant clinical challenge. Although clinicopathological features are commonly utilized, their predictive accuracy remains limited, and the role of multi-gene co-mutations is not fully understood.ObjectiveThis study aimed to develop and validate an integrated risk model that combines next-generation sequencing (NGS) data with clinicopathologic features for the preoperative prediction of LNM in PTC.MethodsWe retrospectively analyzed 521 patients with PTC. Gene mutations were analyzed using NGS. Independent risk factors for central (CLNM) and lateral (LLNM) lymph node metastasis were identified through univariate and multivariate logistic regression analyses.ResultsThe BRAF V600E mutation was the most prevalent (82.15%). Notably, high-risk multi-gene co-mutations —specifically, BRAF V600E co-occurring with TERT, PIK3CA, and/or TP53)—were identified as the strongest independent risk factor for CLNM (odds ratio [OR] = 6.319, 95% confidence interval [CI]: 1.738–22.976, P = 0.005). Other significant risk factors included male sex, age <45 years, bilateral lesions, tumor size >1 cm, lymphovascular invasion (LVI), and extrathyroidal extension,with gross ETE demonstrating the highest ORs (> 21).ConclusionPreoperative NGS profiling, particularly the detection of high-risk multi-gene co-mutations, provides a powerful tool for refined risk assessment. This molecularly guided strategy has the potential to inform personalized surgical planning directly, optimizing the extent of lymph node dissection to improve oncologic outcomes while minimizing unnecessary morbidity.